Determinants of Customers Decision to Choose an Islamic Bank - Indah Sari (Department of Islamic Banking, 2022)
The formulation of the research problem is whether there is an influence of location, service, and promotion on customer decisions in choosing a sharia bank. The discussion in this study is a theory related to location, service, promotion, and customer decisions. This research is a quantitative study, the data source is primary data, data collection using questionnaires and interviews. The research sample consisted of 30 samples with saturated sampling technique, the research analysis used statistics, namely SPSS 20. The results of the study it was found that the variable location had an effect on customer decisions in choosing Islamic banks while the service and promotion has no effect on customer decisions. Then based on the results of the F test, it is known that the variables of location, service, and promotion affect customer decisions in choosing Islamic banks in the Nagasaribu village, Kec. Padang Bolak Tenggara.